2016
DOI: 10.3390/horticulturae3010011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio-Organic and Inorganic Nutrient Sources on Growth and Flower Production of African Marigold

Abstract: African marigold (Tagetes erecta L.) is one of the most important flower crops grown commercially throughout India as a loose flower for worshipping, garland making, and garden display. The productivity and quality of flowers is greatly influenced by the quantity and source of nutrients. At present, these nutrients are primarily supplied through chemical fertilizers. The indiscriminate use and complete reliance on the use of chemical fertilizers has also led to deterioration of soil health, thereby affecting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
4
7
1
1
Order By: Relevance
“…While no specific literature on statice came up, findings similar to the present study have been reported from various studies involving treatments with organic manures on other crops. These findings are supported by Sharma et al (2017) who when working with marigold (var. Pusa Narangi) reported maximum shelf life and flower vase life from treatments that included application of farm yard manure as organic manure alongside bio fertilizers and NPK in integrated plant nutrient management.…”
Section: Effect On Postharvest Qualitysupporting
confidence: 67%
See 1 more Smart Citation
“…While no specific literature on statice came up, findings similar to the present study have been reported from various studies involving treatments with organic manures on other crops. These findings are supported by Sharma et al (2017) who when working with marigold (var. Pusa Narangi) reported maximum shelf life and flower vase life from treatments that included application of farm yard manure as organic manure alongside bio fertilizers and NPK in integrated plant nutrient management.…”
Section: Effect On Postharvest Qualitysupporting
confidence: 67%
“…Similarly, Pansuriya et al (2018) reported significantly enhanced growth and yield parameters in gladiolus from treatment combinations containing bio fertilizers. Sharma et al (2017) also reported increased plant height, number of branches, plant spread, flowering duration and flower yield in African marigold under vermicompost treatments. Abubaker et al (2015) attributed superior plant performance under application of bioslurry to the inhibition of ammonia oxidation and denitrification which potentially benefits crop growth due to reduced losses of soil nitrogen.…”
Section: Effect On Growth and Yieldmentioning
confidence: 78%
“…Bio-fertilizers increase the absorption of the macro and micro nutrients of plant which influences the overall growth of the plant. Significant increase in spread due to application of Azospirillum, and inorganic fertilizers has been reported earlier in Marigold (Sharma et al, 2015).…”
Section: Plant Spread (Cm)mentioning
confidence: 75%
“…Growth and yield of African marigold increases when inorganic fertilizers were supplemented with biofertilizers and organic manures like vermicompost and cow urine. Application of Azospirillum + phosphate-solubilizing bacteria + cow urine (5%) + vermicompost was most effective in increasing vegetative growth and yield attributes[173].Arbuscular mycorrhizal fungi (AMF) constitute a major component of rhi-zosphere microflora in natural ecosystems forming obligate symbiotic associations with many angiosperms, including several medicinal species[174]. AMF enhances the uptake of relatively immobile nutrients by the host plant, particularly P and various micronutrients.…”
mentioning
confidence: 99%